LaNiO3-nanorod/graphene composite as an efficient bi-functional catalyst for zinc–air batteries. Issue 89 (12th September 2016) - Hu, Jie; Liu, Qiunan; Shi, Ziwei; Zhang, Liang; Huang, Hao
Abstract : LaNiO3 -nanorod/graphene composites possess excellent bifunctional electrocatalytic activity and good electrochemical stability for zinc–air batteries. Abstract : Developing low-cost catalysts for high-performance oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is highly desirable. Herein, LaNiO3 nanorods supported on reduced graphene oxide (LNO-NR/RGO) were synthesized via a hydrothermal method, and characterized by XRD, SEM, TEM, XPS, TG and BET. The results show that the LaNiO3 nanorods have a perovskite structure and good dispersion behavior on the RGO sheets. The catalytic activity of the composite for ORR and OER has been studied by using a rotating disk electrode (RDE) technique. LNO-NR/RGO shows better oxygen electrode potential, a maximum cathodic current density of −4.26 mA cm −2 at 1600 rpm was obtained, and the ORR mainly favors a direct four electron pathway. Compared with pure LaNiO3 nanorods and commercial Pt/C, LNO-NR/RGO is more active for OER, a lower onset potential for OER and a bigger anodic current at the same applied potential are observed. The cycle performance and the stabilities of LNO-NR/RGO toward charge/discharge are significantly higher than those of commercial Pt/C in zinc–air batteries. Such excellent catalytic activity is attributed to the synergistic effect between LNO-NR and RGO along with the 1D conduction in the composite.